2011
DOI: 10.1002/prep.201190003
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Highly Insensitive/Reactive Thermite Prepared from Cr2O3 Nanoparticles

Abstract: Section 3.3.1 First Paragraph second sentence:As can be observed, the thermite made of micro-Cr 2 O 3 is much more sensitive to impact than its nano-Cr 2 O 3 counterpart, the sensitivity being however relatively low compared to the one of commonly used organic explosives such as hexogen or octogen.should be read:As can be observed, the thermite made of micro-Cr 2 O 3 is much less sensitive to impact than its nano-Cr 2 O 3 counterpart, the sensitivity being however relatively low compared to the one of commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To satisfy this permanent requirement of nanostructuring and/or developing complex architectured materials, in particular for the Cr 2 O 3 chromium (III) oxide, many processes have been developed. For instance, Cr 2 O 3 material can be synthesized in the form of spherical nanoparticles [10][11][12][13], nanotubes [6], films [8], and porous matrices by means of soft (surfactants) and hard (mesoporous carbon and silica materials, polymeric building) templates [14,15]. To the best of our knowledge, a nanostructured chromium (III) oxide material that is designed at the macroscale (centimeter) has not yet been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy this permanent requirement of nanostructuring and/or developing complex architectured materials, in particular for the Cr 2 O 3 chromium (III) oxide, many processes have been developed. For instance, Cr 2 O 3 material can be synthesized in the form of spherical nanoparticles [10][11][12][13], nanotubes [6], films [8], and porous matrices by means of soft (surfactants) and hard (mesoporous carbon and silica materials, polymeric building) templates [14,15]. To the best of our knowledge, a nanostructured chromium (III) oxide material that is designed at the macroscale (centimeter) has not yet been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, annealed Cr 2 O 3 nanorods could accelerate the thermal decomposition process of cyclotrimethylenetrinitramine (RDX) and reduce the decomposition temperature by 10 C. 9 Another study showed that nanosized Cr 2 O 3 NPs decreased the ignition delay time by a factor of 3.5 (16 AE 2 vs. 54 AE 4 ms) and accelerated the combustion rate (340 AE 10 mm s À1 ) of the Al/Cr 2 O 3 thermite, which was fabricated by Cr 2 O 3 micro-or nanoparticles (F z 20 nm) and Al NPs (F z 50 nm). 10 A number of efforts have been devoted towards the exploration of the catalytic effects of Cr 2 O 3 , and as a burning catalyst, Cr 2 O 3 exhibits excellent catalyst performance. However, studies on the compatibility and thermal decomposition mechanism of nitrocellulose/Cr 2 O 3 NPs have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, two hypotheses can be suggested: the size effect (µm vs. nm) and the electrical properties of the oxidizer component (conductive, semi-conductive, or insulating). Regarding the former, previous works have shown that the use of micrometer-sized oxidizer particles does not have a significant impact on the ESD threshold value compared to oxidizer nanoparticles [33,34]. For example, when Cr 2 O 3 (Sigma-Aldrich, PS > µm, SSA = 3 m 2 /g) and WO3 (Sigma Aldrich, PS = 20 µm, SSA = 1 m 2 /g) microparticles were used in Al nm-based thermites (Al, Nanotechnologies Inc., PS = 50 nm, SSA = 40 m 2 /g), instead of nanoparticles, the ESD threshold was determined to be 0.14 mJ, i.e., widely lower than the ESD value determined in the present case for the Al-nm/ITO µm energetic system (13.70 mJ).…”
Section: Sensitivity Properties Of the Al/ito Energetic Compositesmentioning
confidence: 97%